2017
DOI: 10.1002/2017jd026858
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of the Active Layer Thickness and Permafrost Thermal State Across Qinghai‐Tibetan Plateau

Abstract: The dynamics of permafrost (including the permafrost thermal state and active layer thicknesses (ALT)) across the Qinghai‐Tibetan Plateau (QTP) have not been well understood on a large scale. Here we simulate the ALT and permafrost thermal state using the Geophysical Institute Permafrost Lab version 2 (GIPL2) model across the QTP. Based on the single‐point simulations, the model is upscaled to the entire QTP. The upscaled model is validated with five investigated regions (IRs), including Wenquan (WQIR), Gaize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 78 publications
5
105
2
1
Order By: Relevance
“…Spatial–temporal variability and soil water relations that occur within and among different vegetation types play an important role in eco‐hydrological processes and sustainable development of ecosystems in arid and semi‐arid areas (del Campo et al, ). In addition to the confluence of slope, the characteristics of plant canopies, distribution of plants roots, and soil freezing and thawing processes affected soil water relations between adjacent vegetation types (Ellis et al, ; Grant et al, ; Qin et al, ; Starkloff, Stolte, Hessel, Ritsema, & Jetten, ; Williams, McNamara, & Chandler, ; Zhang et al, ). We found that temporal patterns of VSWC in 0–20 cm soil layer and 0–70 cm soil profile were significantly correlated ( p < .01) among all three vegetation types (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial–temporal variability and soil water relations that occur within and among different vegetation types play an important role in eco‐hydrological processes and sustainable development of ecosystems in arid and semi‐arid areas (del Campo et al, ). In addition to the confluence of slope, the characteristics of plant canopies, distribution of plants roots, and soil freezing and thawing processes affected soil water relations between adjacent vegetation types (Ellis et al, ; Grant et al, ; Qin et al, ; Starkloff, Stolte, Hessel, Ritsema, & Jetten, ; Williams, McNamara, & Chandler, ; Zhang et al, ). We found that temporal patterns of VSWC in 0–20 cm soil layer and 0–70 cm soil profile were significantly correlated ( p < .01) among all three vegetation types (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The depth at which temperature changes by no more than 0.1°C throughout a year is defined as the depth of zero annual amplitude (ZAA) . It depends on factors including soil thermo‐physical properties, surface characteristics and topography.…”
Section: Methodsmentioning
confidence: 99%
“…We used the Geophysical Institute Permafrost Lab (GIPL) model to simulate the dynamics of frozen ground during 1980–2017 at QSH‐1. This model was developed by the Geophysical Institute Permafrost Lab, University of Alaska Fairbanks, and has been widely used to simulate site‐specific or regional thermal conditions of permafrost . It numerically simulates soil temperature dynamics and the depths of seasonal freezing and thawing by solving a one‐dimensional non‐linear heat equation with phase change: H(),xtτ=x()λ(),xtt(),xτx H ( x , t ) is the enthalpy function, which is given by: normalH(),xt=0tC(),xsitalicds+italicLθ(),xt where x ∈ ( x u , x l ) is a spatial variable that changes with depth, x u and x l are the upper and lower boundary of the temperature profile, corresponding to 0 and 100 m; τ ∈ (0, T ) is the temporal variable and t ( x , τ ) is temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations